EFEKTIVITAS COGNITIVE READING STRATEGIES PADA PENINGKATAN PRESTASI AKADEMIK MAHASISWA - Saifullah; Abd Mughni (LP2M Universitas Ibrahimy, 2019)
This study aims to test the effect of cognitive reading strategies to enhance undergraduate students academic achievement. This study used quasi-experimental alternative-treatment design with pretest. There are 63 undergraduate students in psychology class as a subject. The research data obtained from reading comprehension achievement tests and prior knowledge test as co-variable. The reading comprehension achievement tests and prior knowledge test score compare before and after learning process and tested using Ancoca. The results showed that the cognitive reading strategies was significantly improve undergraduate students academic achievement of the experimental group than the control group. For the cognitive reading strategies feasible for implementation.